A preliminary study of the neuroprotective role of citicoline eye drops in glaucomatous optic neuropathy - Roberti, Gloria (Medknow Publications & Media Pvt Ltd, 2014)
PURPOSE: To study the neuroprotective effect of topical citicoline. MATERIALS AND METHODS: Experimental phase to evaluate the ability of citicoline eye drops to reach the vitreous and the retina: The right eyes of 5 mice CD1 were treated with two drops per day for three days of citicoline 1% and 2% (OMK1, Omikron Italia s.r.l.), and then the vitreous was analyzed with the liquid chromatography and spectrometry mass (LC-MS/MS). Clinical phase to determine if topical citicoline is able to delay glaucoma progression, considering perimetric parameters and electro functional tests. Patients were randomized in two groups, OMK1 and OAG. The first group was treated with OMK1 three times per day, plus hypotensive therapy for two months and one month of wash out. The second group was treated only with hypotensive treatment for three months. RESULTS: LC-MS/MS detected the molecule very well, and only OMK1 showed systemic absorption. Thirty-four patients were enrolled, 16 in the OMK1 and 18 in the OAG group. Perimetric parameters showed a positive trend in individual eyes of patients in OMK1 group, but these values were not statistically significant in the whole group. Retinal ganglion cells function improved as shown by reduced P50 latency (P = 0.04) and increased P50-N95 amplitude (P < 0.0001) of pattern electroretinogram, up to 30 days after the washout (P = 0.01; P = 0.002). Visual evoked potential and retino-cortical time improvement regressed after 30 days of washout. In OAG group, there was any change during the follow-up. No adverse reactions were reported in both groups. CONCLUSIONS: Topical citicoline seems to have a neuroprotective action.